Exfoliation of graphite into graphene in aqueous solutions of inorganic salts - Parvez, Khaled; Wu, Zhong-Shuai; Li, Rongjin; Liu, Xianjie; Graf, Robert; Feng, Xinliang; Muellen, Klaus (Journal of the American Chemical Society, 2014)
Mass production of high-quality graphene sheets is essential for their practical application in electronics, optoelectronics, composite materials, and energy-storage devices. Here we report a prompt electrochemical exfoliation of graphene sheets into aqueous solutions of different inorganic salts ((NH 4)2SO4, Na2SO4, K 2SO4, etc.). Exfoliation in these electrolytes leads to graphene with a high yield (>85%, ≥3 layers), large lateral size (up to 44 μm), low oxidation degree (a C/O ratio of 17.2), and a remarkable hole mobility of 310 cm2 V-1 s-1. Further, highly conductive graphene films (11 Ω sq-1) are readily fabricated on an A4-size paper by applying brush painting of a concentrated graphene ink (10 mg mL-1, in N,N′-dimethylformamide). All-solid-state flexible supercapacitors manufactured on the basis of such graphene films deliver a high area capacitance of 11.3 mF cm-2 and an excellent rate capability of 5000 mV s-1. The described electrochemical exfoliation shows great promise for the industrial-scale synthesis of high-quality graphene for numerous advanced applications. © 2014 American Chemical Society.
CRIS-Team Scopus Importer:2023-03-20